Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.3390/ma6115016
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure of Haynes® 282® Superalloy after Vacuum Induction Melting and Investment Casting of Thin-Walled Components

Abstract: The aim of this work was to characterize the microstructure of the as-cast Haynes® 282® alloy. Observations and analyses were carried out using techniques such as X-ray diffraction (XRD), light microscopy (LM), scanning electron microscopy (SEM), transmission electron microscopy (TEM), X-ray spectroscopy (EDS), wave length dispersive X-ray spectroscopy (WDS), auger electron spectroscopy (AES) and electron energy-loss spectrometry (EELS). The phases identified in the as-cast alloy include: γ (gamma matrix), γʹ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(32 citation statements)
references
References 36 publications
2
29
1
Order By: Relevance
“…However, the TEM images in Figure 9 show homogeneously distributed c′-particles with a globular shape in the cast alloy before creep, so the results of Sajjadi et al [10] are not applicable to this study. e average size of the precipitates was 39 nm, which is smaller than that reported by Matysiak et al [5] (70-110 nm), who investigated the same alloy directly after thin-walled wedge permanent casting in which coarsening of c′-particles occurred. In this study, however, c′-particles fully dissolved during solution treatment after casting; a dense precipitation of nely distributed c′-particles formed during the two-step ageing treatment following by quenching.…”
Section: Tensile Test Resultscontrasting
confidence: 41%
See 1 more Smart Citation
“…However, the TEM images in Figure 9 show homogeneously distributed c′-particles with a globular shape in the cast alloy before creep, so the results of Sajjadi et al [10] are not applicable to this study. e average size of the precipitates was 39 nm, which is smaller than that reported by Matysiak et al [5] (70-110 nm), who investigated the same alloy directly after thin-walled wedge permanent casting in which coarsening of c′-particles occurred. In this study, however, c′-particles fully dissolved during solution treatment after casting; a dense precipitation of nely distributed c′-particles formed during the two-step ageing treatment following by quenching.…”
Section: Tensile Test Resultscontrasting
confidence: 41%
“…e particles observed in the grain interiors and grain boundaries are MC-type carbides, such as (Ti,Mo)C; Cr-rich carbides (presumably M 23 C 6 ) precipitated preferentially in interdendritic regions and grain boundaries. Matysiak et al [5] investigated the cast microstructure of the same alloy and reported that the secondary phases were mostly (Mo/Cr)-rich carbide and the c′-phase of (Ni, Ti)Al. ey also reported that the c′-phases precipitated as a round shape (size: 70 nm) in dendritic regions and as a cubic shape (size: 110 nm) in interdendritic regions.…”
Section: Microstructurementioning
confidence: 99%
“…Haynes 282 is classified as c¢-strengthened wrought superalloy (but, it is also under consideration as a cast alloy for fabrication of casings and thin-walled components (Ref 4,5)). Its mechanical properties are controlled by the heat treatment containing the solutionizing followed by aging processes.…”
Section: Introductionmentioning
confidence: 99%
“…The microstructural analyses of the HAZ reveled possible evidence of a secondary phase distributed ahead of the propagating cracks in the Haynes® 282® samples. This secondary phase can be the same as distributed interdendritically in the FZ identified in other studies [5,16] as Ti-Mo based MC-type carbides with an FCC crystal structure. MC carbides were found randomly distributed intergranularly and intragranularly within γ phase with typical size in the range of 2-15 µm.…”
Section: Varestraint Testmentioning
confidence: 50%